The impact of academically and socially focused peer relations on children’s engagement and academic progress in primary school - Baines, Edward; Somerville, Matthew; Böheim, Ricardo; Pervez, Aneeza; Zhao, Yue; Symonds, Jennifer; Davies, Aisling; Blatchford, Peter (Frontline Learning Research, 2025)
Previous research suggests connections between peer relationships and children’s engagement and learning within the classroom. However few studies have explored these connections in detail or considered the possible processes that may begin to explain the linkages. This study collected systematic data from different respondents within primary school settings to help clarify the role of peers in classroom engagement and learning. Over 800 pupils based in English primary schools were involved in a multi-method study. Peer-sociometric questionnaires provided measures of academic peer relations, informal-social peer relations, such as being accepted as a work partner and liked as a person to play with, playground group centrality and leadership. Self-report questionnaires provided data on school engagement, disengagement, and disaffection. Science attainment data were collected at the start and end of the year. Momentary behavioural engagement was observed in classrooms for a subsample of pupils who were also rated by their teachers in terms of their attention and behaviour in class. Findings revealed small to moderate associations between peer relations measures, multiple measures of school and classroom engagement, attainment, and progress. Multiple regressions examined peer relations measures relative to momentary, classroom and school engagement and learning outcomes. Findings highlight important overlaps and differences in the predictors of different types of engagement. They also highlight the variety of ways in which peer relationships, whether academically or socially focused, may have different implications for engagement at momentary, classroom, and school levels. Findings indicate that academic peer acceptance is predictive of engagement at the different levels and science attainment. However, informal-social peer relations were more highly connected with class disruption, school disengagement and disaffection and were negative predictors of attainment and progress over the year. This suggests different pathways for children with different types of relationships with peers relative to engagement and adjustment highlighting complex connections between social and academic life in school.